Teologi Bakti Bulanan di GKPI dan Implikasinya Bagi Jemaat yang Tidak Membayar Bakti Bulanan di GKPI Singkamjulu - Sri Devita Hutasoit; Iwan Setiawan Tarigan (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
Giving thanks is a form of faith in God's promises, to give the best to people who already love him. Therefore, someone can give thanks because they have sensitivity to God's grace. Giving offerings is a form of giving thanks to God and a human responsibility that comes from the motivation in the heart to be grateful for God's actions in human life. One form of offering as thanksgiving to God is giving monthly devotion to the church. Monthly devotion is one of the offerings that has been established at GKPI. Monthly devotion itself is an obligation as a member of the church congregation and as a source of church income. This aims to continue service activities in the midst of the church. When the congregation gives offerings as its monthly service, the congregation gives thanks for what it receives from God through every work or other. However, the monthly service itself has rules that have been set by the GKPI Head Office to discipline the congregation and church. When a congregation does not follow the monthly service rules that have been determined, it can be said that the congregation is not obeying the rules. This is also one of the congregation's shortcomings in supporting existing services in the church. Meanwhile, this monthly devotion is an obligation as a member of the congregation.